Assessment of Long-Term Effects and Patient Satisfaction following TMJ Disc Replacement Surgery - Mohammed Ibrahim; Samir Mansuri; Pradeep Kumar; Brajesh Gupta; Yogita Mundada; David Tyro; Vinej Somaraj (Wolters Kluwer Medknow Publications, 2024)
Objectives: The purpose of this research is to evaluate patient satisfaction and long-term consequences after temporomandibular joint (TMJ) disc replacement surgery in a tertiary care environment. Methods: 500 patients who had TMJ disc replacement surgery at a tertiary care facility between 2010 and 2015 were the subject of a retrospective investigation. Pre-operative clinical features, demographic information, and intraoperative information were gathered. Standardized measurements were used to evaluate functional results, pain levels, and patient-reported outcomes. Descriptive statistics, paired t-tests, and significance set at P < 0.05 were all used in the statistical analysis. Results: There were notable improvements in functional outcomes, with a mean increase in lateral excursion from 8.7 mm to 12.6 mm (P < 0.001) and maximal incisal opening from 30.5 mm to 40.2 mm (P < 0.001). The pain level was found to have greatly diminished, as evidenced by the VAS scores falling from 7.8 to 3.2 (P < 0.001). The Jaw Function Limitation Scale scores (42.6 to 21.8, P < 0.001) and patient-reported outcome measures scores (58.3 to 76.5, P < 0.001) exhibited significant increases in patient-reported outcomes. Conclusion: In conclusion, tertiary care TMJ disc replacement surgery shows positive long-term outcomes, such as enhanced jaw function, less discomfort, and high patient satisfaction. This research supports the ongoing use of TMJ disc replacement surgery as a potential therapy for refractory TMJ disease, although noting its limitations.